Ecological Research for Studies of Violence: A Methodological Guide. Issue 23 (December 2019) - Zeoli, April M.; Paruk, Jennifer K.; Pizarro, Jesenia M.; Goldstick, Jason
Ecological research is important to the study of violence in communities. The phrases "ecological research" and "ecologic study" describe those research studies that use grouped or geographic units of analysis, such as zip codes, cities, or states. This type of research allows for the investigation of group-level effects and can be inexpensive and relatively quick to conduct if the researcher uses existing data. And, importantly, ecological studies are an efficient means for hypothesis generation prior to, and can be used to justify, costlier individual-level studies. Ecological research designs may be employed to study violence outcomes when the research question is at the population level, either for theoretical reasons, or when an exposure or intervention is at the population level, or when individual-level studies are not feasible; however, ecological research results must not be used to make individual-level inferences. This article will discuss reasons to conduct ecological-level research, guidelines for choosing the ecological unit of analysis, frequently used research designs, common limitations of ecological research, including the ecological fallacy, and issues to consider when using existing data.